2020
DOI: 10.3758/s13414-020-02131-x
|View full text |Cite
|
Sign up to set email alerts
|

The metronome response task for measuring mind wandering: Replication attempt and extension of three studies by Seli et al

Abstract: Science requires replicable tools to measure its intended constructs. Attention research has developed tools that have been used in mind-wandering research, but mind-wandering measures often rely on response-inhibition, which introduces speed-accuracy trade-offs that may conflate errors for mind-wandering. We sought to replicate three studies that used an improved mindwandering measure: the Metronome Response Task (MRT). In a large (N=300) multisite sample, the primary MRT finding was replicated, showing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…Additionally, we found that higher rates of motivation were associated with better performance on the MRT task. This latter result is notable in that a recently attempted conceptual replication of Seli et al (2013) failed to find an association between overall rates of motivation and overall performance on the MRT task (Anderson, Petranker, Lin, & Farb, 2020). Here, we do find a significant association.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we found that higher rates of motivation were associated with better performance on the MRT task. This latter result is notable in that a recently attempted conceptual replication of Seli et al (2013) failed to find an association between overall rates of motivation and overall performance on the MRT task (Anderson, Petranker, Lin, & Farb, 2020). Here, we do find a significant association.…”
Section: Discussionmentioning
confidence: 94%
“…Besides self-reported attentional lapses, one of the objective measures (i.e., the RT variability in the MRT) also contributed to the explanation of the WPR. The MRT is typically used as an alternative, more objective measure of attentional lapses ( Anderson et al 2021 ; Seli et al 2013 ). However, Figure 4 and Figure 5 show that the MRT explained not only the slope of the WPR but also large parts of the covariances and correlations over the whole RT distribution.…”
Section: Studymentioning
confidence: 99%
“…For example, throughout a task, we may feel more on-task on some moments and more off-task on others. It has been found that these fluctuations in subjective attentional state correlate locally with fluctuations in performance (e.g., consistency during synchronised tapping), which deteriorates when one feels more off-task (Anderson et al, 2021;Laflamme et al, 2018;Seli et al, 2013;Thomson et al, 2014).…”
Section: Attentional Statementioning
confidence: 99%
“…Consistent with this, we find that data the MRT, which is also time-estimation-based, showed relatively high structure. Anderson et al, 2021), participants who did both the SART and Visual Search task (Jin et al, 2019)…”
Section: Part 1: Establishing the Presence Of Temporal Dependenciesmentioning
confidence: 99%
See 1 more Smart Citation